Hard X-ray photoelectron spectroscopy of new materials for spintronics - Fecher, Gerhard H.; Felser, Claudia (Springer Netherlands, 2013)
In this work, results of hard X-ray photoelectron spectroscopy (HAXPES) of Heusler compounds and new materials for spintronics are presented. The class of Heusler materials includes some interesting half-metallic and ferromagnetic properties that were predicted by theory. HAXPES allows a direct comparison of the measured and the calculated electronic structure. Valence band spectroscopy of bulk materials by HAXPES is illustrated for the case of the half-metallic ferromagnet Co2MnGe. The feasibility of HAXPES to explore the valence band electronic structure in deeply buried metallic layers is demonstrated for buried Co2MnSi films. The films exhibit the same valence density of states as bulk samples and confirm the promise of an epitaxial, single-crystalline Co2-based Heusler compound film as a ferromagnetic electrode for spintronics devices. The study of complete CoFe(B)/MgO/CoFe(B) tunneling junctions demonstrates the capability of HAXPES to explore the electronic structure in deeply buried layers in a non-destructive way. The improvement of the TMR by annealing of the junction is explained by an improvement of the structure together with a change of the composition in the CoFeB layers.
CRIS-Team Scopus Importer:2023-03-20